Law Due To Certificate Issuance Rights Of Land Management (HPL) No. 1 Of 1987 The Land Of Tradition (In Dignity Justice Theory Perspective) - Roximelsen Suripatty; Siti Muzazanah; Munsharif Abdul Chalim (Jurnal Akta, 2019)
This article provides an analysis Descriptive just about any Rights Land Stewardship (HPL) and the state of the legal regulation of HPL on community land. Research findings is that it turns out the existence of Land Management Rights, by society in general considered to be problematic from a legal setting. In view of the general public (the men in the street) there is no clear basis in the legal arrangements of the Basic Agrarian Law regarding the HAT. Problems HPL also appear as the result of legal research normative author, with mainly navigated by Justice Theory Dignity (the dignified Justice Theory) was found that the provision HAT to the Government almost be violate or conflict with the rights to other land that had previously existed. As for the other HAT referred to are the property of land under customary law. The ownership of the land under customary law was legally recognized. In this study also found that in fact the birth of HPL owned by the Government of Sorong regency which has now become the City of Sorong on the one hand is based on the claim the Government of Sorong, proposed by the elements of the local Land Office that the origin of the HPL is a conversion from HAT in West Law (Right Erfpacht). With this fact it can be said that the Government HPL Sorong seek refuge or shelter behind Erfpact Verponding. In fact, in a Court decision expressly states that the right Erfpach judges and Erfpacht Verponding it is not there anymore. The legal consequence is Erfpacht not be used as legal basis that justifies or justification for HPL. According to the Judge, HPL Sorong government owns comes from the State Land. In short it can be said that this article contains an overview of the issues HPL law above the government-owned land parcels at the same time also be claimmerupakan land belonging to indigenous peoples. Keywords: Because of law Rights Land Stewardship; Indigenous Lands; Justice.